Wandering decarbonization : the BRIC countries as conservative climate powers - Viola, Eduardo (2016)
This article discusses the role of China, Russia, India and Brazil in the climate regime. It describes the trajectory of their emissions, of their domestic policies and of their international commitments, and argues that, despite their responsibility in causing the problem, they have been conservative forces in the climate regime.